Divisions in Treaty 6 Perspectives: the dilemma of written text and oral tradition - Wing, Miriam Lily (MacEwan University Student eJournal, 2016)
Since the signing of Treaty 6 in 1876, there has been ongoing controversy between the First Nations and the Canadian government regarding the understanding and fulfillment of the treaty terms. Through investigating both historical texts and oral tradition, this article hopes to give insight on the modern dilemma of treaty rights in the specific case of Treaty 6. In order for the most accurate understanding of Treaty 6 to be obtained, First Nations oral tradition and perspectives must be considered as valid evidence.